Pengaruh Pelatihan dan Kompetensi terhadap Kinerja SDM pada UMKM Kabupaten Probolinggo - Achmad Basofitrah (JSE: Jurnal Sharia Economica, 2026)
The performance of human resources (HR) in Micro, Small, and Medium Enterprises (MSMEs) in Probolinggo Regency remains low, as indicated by limited production skills, weak managerial capabilities, and inconsistent service quality. Data from the Department of Cooperatives and MSMEs (2023) show that 62% of MSMEs experience stagnation due to insufficient competencies and the limited implementation of training outcomes. Despite various training programs provided by the local government, their effectiveness has not yet produced measurable improvements. Furthermore, empirical studies on rural MSMEs characterized by distinct socio-cultural contexts and limited governmental support remain scarce, creating an important research gap. This study aims to analyze the influence of training and competence on HR performance among MSMEs in Probolinggo Regency. A quantitative approach was employed using a survey of 100 MSME actors selected through purposive sampling, with data analyzed using multiple linear regression. The findings reveal that training has no significant effect on HR performance, while competence exerts a significant and dominant influence. These results indicate that improving MSME HR performance is more effectively achieved through strengthening technical and managerial competencies rather than short-term, generic training programs. The study recommends evaluating existing training designs and developing competency-based HR strategies aligned with the operational needs of MSMEs in Probolinggo.